2018
DOI: 10.1097/md.0000000000013902
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dietary patterns, supplements intake and autism spectrum disorders

Abstract: The aim of this study was first to investigate associations between maternal dietary patterns and autism spectrum disorders (ASDs) and second to investigate association between maternal supplement intake and ASD.We used a case-control study design to enroll typically developing (TD) children and children with ASD, and data were derived from the Autism Clinical and Environmental Database (ACED).Three seventy four children with AUTISM and 354 age matched TD children were included. The multivariate logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(73 citation statements)
references
References 37 publications
4
69
0
Order By: Relevance
“…We also observed a relation with nutritive supplements and reproductive hormones. Increased and decreased risk of ASD has been previously reported for medications from these groups [32,33]. Maternal metabolic conditions and disruptions in the endocrine system have been associated with ASD-risk [32,33], and contributed to case classification.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We also observed a relation with nutritive supplements and reproductive hormones. Increased and decreased risk of ASD has been previously reported for medications from these groups [32,33]. Maternal metabolic conditions and disruptions in the endocrine system have been associated with ASD-risk [32,33], and contributed to case classification.…”
Section: Discussionmentioning
confidence: 97%
“…Increased and decreased risk of ASD has been previously reported for medications from these groups [32,33]. Maternal metabolic conditions and disruptions in the endocrine system have been associated with ASD-risk [32,33], and contributed to case classification. Taken together, the agreement between our most useful features with previous studies analyzing ASD patients increases the confidence in our combined approach.…”
Section: Discussionmentioning
confidence: 97%
“…Of the cohort studies, 3 relied on prospectively selfreported FA supplement use, including 2 analyses in the DNBC [Strom et al, 2018;Virk et al, 2016], and 1 in the SYC cohort [DeVilbiss et al, 2017]. Of the case control studies, one relied on retrospectively self-reported information [Y. M. Li et al, 2018], and one on national registry data [Sharman Moser et al, 2019]. Lastly, two studies assessed offspring autistic traits and maternal folate concentration using biomarkers from blood samples collected during pregnancy from the HOME cohort [Braun Results across the rapidly growing number of folate/FA supplementation studies therefore suggest that, while protective associations have been replicated, there is also a fair degree of conflicting information.…”
Section: Fa/folatementioning
confidence: 99%
“…We identified three studies evaluating associations between combined dietary factors or dietary patterns and ASD [L. Gao, Cui, et al, 2016;House et al, 2018;Y. M. Li et al, 2018].…”
Section: Dietary Patterns/habitsmentioning
confidence: 99%
“…In individuals with a genetic predisposition, a range of environmental factors have been proposed to increase ASD risk [7,12]. Among them are variations in maternal metabolism at pregnancy [13,14]. Beside maternal metabolism, adverse health conditions during early pregnancy such as viral infections, inflammation, and immune activation are considered as risk factors for psychiatric disorders in the offspring [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%